2006
DOI: 10.1099/vir.0.81815-0
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity variation and genetic diversity among strains of Western equine encephalitis virus

Abstract: Variation in infectivity and genetic diversity in the structural proteins were compared among eight strains of Western equine encephalitis virus (WEEV) to investigate WEEV virulence at the molecular level. A lethal intranasal infectivity model of WEEV was developed in adult BALB/c mice. All eight strains examined were 100 % lethal to adult mice in this model, but they varied considerably in the time to death. Based on the time to death, the eight strains could be classified into two pathotypes: a high-virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 31 publications
2
40
0
2
Order By: Relevance
“…Forrester et al (2008) demonstrated that only one of ten WEEV isolates (CR46) caused .50 % mortality in subcutaneously infected Swiss-Webster mice (age of mice not given). The MTD of IMP when infected via aerosol was 7 days, considerably longer than any of the isolates tested by Nagata et al (2006), and the survival rate was 90 %. Bianchi et al (1993) also infected outbred Swiss NIH mice (28-32 days old) with similar doses, but using the intracranial and intraperitoneal routes of infection, and showed that Virulence variation among WEE viruses in mice neuroinvasiveness was uniquely associated with epizootic strains of WEEV.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Forrester et al (2008) demonstrated that only one of ten WEEV isolates (CR46) caused .50 % mortality in subcutaneously infected Swiss-Webster mice (age of mice not given). The MTD of IMP when infected via aerosol was 7 days, considerably longer than any of the isolates tested by Nagata et al (2006), and the survival rate was 90 %. Bianchi et al (1993) also infected outbred Swiss NIH mice (28-32 days old) with similar doses, but using the intracranial and intraperitoneal routes of infection, and showed that Virulence variation among WEE viruses in mice neuroinvasiveness was uniquely associated with epizootic strains of WEEV.…”
Section: Discussionmentioning
confidence: 95%
“…By using the intracranial and intraperitoneal routes, others have shown that enzootic isolates of WEEV from California were not uniformly of low pathogenicity and could show a range of virulence in adult mice (Hahn et al, 1988). Nagata et al (2006) reported 100 % mortality in each of eight isolates of WEEV by the intranasal route in adult BALB/c mice, although there was variation in MTD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Comparisons of isolates from North and South America reveal several antigenic subtypes and viral lineages, 7,8 with variation in virulence in rodent models of disease. [9][10][11] In North America, EEEV circulates between birds and Cx. melanura or other mosquitoes, but transmission to humans or horses can occur through Aedes, Coquillettidia, or Culex mosquito species that feed on both birds and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Like in humans, age and strain of mouse infected, route of inoculations, and virulence of virus strain all influence the susceptibility of the host (Aguilar, 1970;Bianchi, et al, 1993;Logue, et al, 2009;Monath, et al, 1978;Nagata, et al, 2006). Peripheral routes of infection result in approximately 50% mortality with intracerebral (IC) or intranasal (IN) challenge resulting in more uniform, dose-dependent mortality depending on strain of virus and background of murine model (Hardy, et al, 1997;Julander, et al, 2007;Liu, et al, 1970).…”
Section: Mouse Modelmentioning
confidence: 99%